Students' Experiences in Using Zoom-Based Learning to Enhance English Speaking Skills in EFL Classrooms - Salsabila, Citra Umi Kultsum; Zahwa, Defarra Al; Sholiha, Naila Bilqis; Putra, Aidil Syah (Lembaga Penelitian dan Pendidikan Mandala, 2026)
This study investigates English Education students’ experiences in using Zoom-based learning to enhance English speaking skills in an EFL classroom context. A qualitative descriptive design was employed with nine undergraduate students from the English Education Study Program at the University of Muhammadiyah Tangerang, Indonesia. Data were collected through semi-structured interviews conducted via Zoom in mixed Indonesian–English to support comfortable expression. All interviews were recorded using Zoom’s built-in recording feature, transcribed verbatim, and analyzed through thematic analysis to identify recurring patterns. The findings indicate that Zoom facilitates speaking practice by increasing opportunities for structured interaction, particularly through breakout rooms and guided discussions, and by enabling flexible participation via audio, video, and chat. Students also valued screen sharing for organizing ideas and sustaining talk during tasks. Nevertheless, participants reported constraints that hindered performance, including unstable internet connection, audio delay, reduced spontaneity due to limited non-verbal cues, and anxiety when speaking on camera or being recorded. Overall, Zoom-based learning can contribute to speaking development when instructors design interactive, turn-rich tasks, manage turn-taking clearly, and provide supportive, focused feedback. Creating a psychologically safe climate and preparing technical contingencies are recommended to reduce anxiety and maintain engagement in online speaking classes in this participant cohort.